Beginning Silverlight 2 From Novice to Professional - Lair, Robert (Apress : Imprint: Apress, 2009)
With the need for a richer user experience ever more in focus when creating web applications, Microsoft has released Silverlight, the new cross-browser, cross-platform plug-in that allows developers to create rich interactive applications for the Web. Silverlight poses exciting new opportunities for creating visually impressive web applications, offering unparalleled response times and minimal bandwidth requirements. Key differences in the new design tools present developers with new challenges, but author Robert Lair of IBuySpy notoriety (the original ASP.NET application) shows you how to get a firm handle on Silverlight so you can start creating your own Silverlight web applications with exciting results. Explore the best of the new tools and discover how they can benefit your own projects. Microsoft's Expression Design tool plays an important part in creating Silverlight assets, Microsoft Expression Blend is used to build user interaction for Silverlight elements, and Microsoft Visual Studio 2008 manages the interaction between designers and developers and provides the coding environment for the "nuts and bolts" basis of Silverlight development. Prepare to take a grand tour of all these new tools and explore the fundamentals of building good Silverlight applications from scratch. Once you've mastered the basics, you'll move on to a more in-depth discussion of some of the groundbreaking new features of the Silverlight technology and why they will change the way you build web sites of the future.